ANALISIS PERILAKU KONSUMEN MUSLIM GENERASI MILENIAL TERHADAP KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) PRODUK HALAL - Putri, Nike Anita; Firmansyah, Egi Arvian (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2021)
This research aims to primarily determine the factors that influence willingness to pay for halal products among Muslim Millennial Generation. Besides, it aims to explore the effect of willingness to pay for halal products on demand for Halal certification. Descriptive and Explanatory methods with a quantitative approach are used in this research. The sample in this study consists of 495 Millennial Muslims aged from 18–36 years old, collected using convenience sampling/accidental sampling. Data are analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). The result of this research shows that factors such as halal concern, attitude, religiosity, and product composition significantly affect willingness to pay, while the perception of the halal process and subjective norms do not significantly influence it. Also, the variable willingness to pay has a significant influence on the demand for halal certification.